2002
DOI: 10.1046/j.1365-2575.2002.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the successful adoption and use of IS/IT in SMEs: an explanation from Portuguese manufacturing industries

Abstract: The objectives of the research were to identify factors enabling or inhibiting the adoption and use of information systems and technology (IS/IT) in Portuguese manufacturing small and medium-sized enterprises (SMEs) and understand how these factors interrelate in determining relative success in the adoption and use of IS/IT. This research elicited factors from previous quantitative and qualitative research, which had been shown to influence IS/IT adoption in SMEs in other contexts. A strategic change framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(169 citation statements)
references
References 37 publications
9
152
1
7
Order By: Relevance
“…This finding suggests that the quality of service does not influence the use of the system. This is inconsistent with previous studies where service quality is reported to have a significant influence on system use (Caldeira & Ward 2002;Fitzgerald & Russo 2005).…”
Section: Structural Modelcontrasting
confidence: 99%
“…This finding suggests that the quality of service does not influence the use of the system. This is inconsistent with previous studies where service quality is reported to have a significant influence on system use (Caldeira & Ward 2002;Fitzgerald & Russo 2005).…”
Section: Structural Modelcontrasting
confidence: 99%
“…Finally, lack of skills and technical and managerial expertise (Caldeira and Ward, 2002;Matthews, 2007;Dyerson et al, 2009;Qureshil et al, 2009) It is noteworthy however that the skills required for implementing ICT may be held by a person other than the manager. In general, the presence of an "expert" user, whether executive or another member of the company is likely to reduce the technological expertise barrier and facilitate the adoption of ICT tools.…”
Section: The Role Of Small Firms Managers In the Use Of Ictmentioning
confidence: 99%
“…Chircu & Kauffman (2000) find that lack of ability to acquire skill and expertise in new technologies combined with a lack of training and education form significant barriers to the adoption of e-business technologies. In the context of SMEs, the organizations that possess digital competence are more likely to accept innovations as they have a better understanding of the benefits of such innovations than if such competences were lacking (Caldeira & Ward, 2002). Indeed, Caldeira & Ward (2002) conclude that for SMEs to successfully adopt IEBT, their executives and employees must have a reasonable knowledge of the relevance of IS in business operations.…”
Section: Digital Competence In Smesmentioning
confidence: 99%
“…In the context of SMEs, the organizations that possess digital competence are more likely to accept innovations as they have a better understanding of the benefits of such innovations than if such competences were lacking (Caldeira & Ward, 2002). Indeed, Caldeira & Ward (2002) conclude that for SMEs to successfully adopt IEBT, their executives and employees must have a reasonable knowledge of the relevance of IS in business operations.…”
Section: Digital Competence In Smesmentioning
confidence: 99%